Black Spruce (Picea mariana) Regeneration in Post-fire Cryptogamic Mats - Kayes, Imrul (2016)
Post-fire black spruce (Picea mariana Mill.) regeneration has received considerable attention in management of the boreal forest of eastern Canada. Seedbed quality is a key factor for seed germination and early seedling establishment. The objective of this research was to investigate the potential role of cryptogamic seedbeds in black spruce germination and seedling establishment. To compare lichen-dominated seedbeds with thin and thick organic matter, in situ seeding experiments were conducted at three sites in Terra Nova National Park, Newfoundland burned 11 (Rocky Pond, RP), 17 (Spracklin Road, SR) and 37 (Terra Nova Road, TNR) years ago. At each site, three manipulation treatments (mat-intact, mat-mixed and mat-removed) were applied to the seedbed with four replications in plots of 30 x 30 cm where 200 black spruce seeds were broadcasted. To compare lichen vs. moss seedbed, the same experimental design was extended to moss dominated seedbeds at the SR site. A laboratory germination bioassay was conducted to test the possible chemical effects of four cryptogamic species on black spruce germination and primary growth. Seed germination was highest in mat-intact and mat-removal plots with thick OM at RP, mat-mixed plots with thin OM at SR and matmixed plots with both thin and thick OM at TNR. There was significantly higher germination and seedling establishment on moss seedbeds than lichen seedbeds. In moss seedbeds, mat-mixed plots with thick OM had the highest germination but mat-intact plots of both thin and thick OM had higher seedling establishment. Moss seedbeds had higher soil moisture and lower surface temperature than lichen seedbeds. Laboratory bioassay with lichen Cladonia cristatella Tuck. had significantly lower germination and seedling growth than control but no difference between the control and moss treatments. HPLC analysis of C. cristatella indicated the presence of a germination inhibiting allelochemical, usnic acid. Lichen mat provides physical barrier to seed germination and seedling growth in late post-fire site TNR but not in early post-fire sites. It appears that moss dominated seedbeds facilitate black spruce regeneration by increasing seedbed moisture retention and maintaining low surface temperature, while lichen seedbeds inhibit seedling regeneration by their adverse physical and chemical effects. Cryptogamic seedbed type, OM thickness, soil moisture and temperature are limiting factors in poor black spruce seedling regeneration after fire.